2016
DOI: 10.1002/cpp.2023
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Co‐rumination and Internalizing Problems: A Systematic Review and Meta‐analysis

Abstract: Co-rumination has maladaptive (repetitive, unproductive discussion of problems) components, but also shows an association with friendship satisfaction. The current review found that co-rumination has small-moderate association with depression and anxiety. Practitioners should be aware of the way in which people discuss affective distress with others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 57 publications
6
75
2
1
Order By: Relevance
“…Social support seeking may be more effective in ameliorating depressive symptoms among emerging adults relative to adolescents as a result of more mature neural circuitry supporting improved social cognition abilities that facilitate communication (Burnett & Blakemore, 2009). Adolescents’ ability to communicate their needs and determine the most appropriate source of support also may be adversely impacted by relatively underdeveloped executive functioning skills (Burnett & Blakemore, 2009), as well as a lack of social experience or use of maladaptive social support strategies such as co-rumination (Spendelow, Simonds, & Avery, 2016). Both adolescents and emerging adults report an increased reliance on peers (vs. family members) for support (Amirkhan & Auyeung, 2007; Gelhaar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Social support seeking may be more effective in ameliorating depressive symptoms among emerging adults relative to adolescents as a result of more mature neural circuitry supporting improved social cognition abilities that facilitate communication (Burnett & Blakemore, 2009). Adolescents’ ability to communicate their needs and determine the most appropriate source of support also may be adversely impacted by relatively underdeveloped executive functioning skills (Burnett & Blakemore, 2009), as well as a lack of social experience or use of maladaptive social support strategies such as co-rumination (Spendelow, Simonds, & Avery, 2016). Both adolescents and emerging adults report an increased reliance on peers (vs. family members) for support (Amirkhan & Auyeung, 2007; Gelhaar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Male and female mentees tend to be referred to mentoring programs for different reasons, with male referrals more commonly stemming from the need for a male role model, while female mentees are more often referred because of relational challenges with their primary caregivers (Rhodes et al 2008). Moreover, there is some indication that, relative to males, females are more prone to co-rumination in their dyadic relationships, a process that could attenuate positive effects (Splendelow et al 2017). Consistent with these ideas, DuBois and colleagues' (2011) meta-analysis demonstrated that programs serving a greater proportion of male mentees had stronger effects.…”
Section: Youth Characteristicsmentioning
confidence: 99%
“…The general form of co-rumination has been linked to higher internalizing symptoms [50]. Although corumination has been associated with greater psychological difficulty concurrently and prospectively, there are no current studies examining general co-ruminative practices in individuals with EDs.…”
Section: Ruminationmentioning
confidence: 99%